Notes from Underground and “Masha is lying on the table…” Experience of “Close Reading” in a Close Context - Tatiana A. Kasatkina (Russian Academy of Sciences. A.M. Gorky Institute of World Literature, 2018)
The diary note of F.M. Dostoevsky “Мasha is lying on the table. Will I see Masha again?..” is recognized by some researchers as the close context of “Notes from Underground”, but this context turns out to be problematic, sometimes they say: “It’s incomprehensible how these two texts, written with one hand, can coexist in the same time?” In the article I attempt read the diary note “Masha is lying on the table...” using the method of close reading to reveal not only the common problems in it (as well as in “Socialism and Christianity”) and in “Notes from the Underground”, but also to reveal those common decisions, which Dostoevsky offers in the texts in question. During the process it becomes obvious that Dostoevsky brings in these ideas in the text completely implicitly, through the hero’s speech, they aren’t imposed on to the reader; the necessity (and even, to some extent, the inevitability for the human existence) of “faith and Christ” is concealing in the speeches of the character which seem “most nihilistic”. The method of “slow/close reading” proves to be the most adequate for considering these works in the immediate context, because Dostoevsky’s diary notes have a great semantic density, high degree of suggestibility, and it is impossible to see their connection with the artistic works of Dostoevsky of the same period if taking them “in general”. The article deals with the categories of Dostoevsky’s philosophy such as “I” and “all”, Dostoevsky’s solution of the problem of the goal of human life, and the problem of wholeness of “Notes from the Underground”.